MICROBIAL CONTRIBUTIONS TO N-IMMOBILIZATION AND ORGANIC MATTER PRESERVATION IN DECAYING PLANT DETRITUS - Tremblay L.; Benner R. (My University, 2006)
Microbial contributions to the detritus of two vascular plant tissues, smooth cordgrass (Spartina alterniflora) and black mangrove leaves (Avicennia germinans), were estimated over a 4-year decomposition period under subaqueous marine conditions. During this period, 93-97% of the initial plant tissues was decomposed. Bulk elemental and isotopic compositions of the detritus were measured along with hydrolyzable amino sugars (AS) and amino acids (AA), including the bacterial biomarkers muramic acid and the d-enantiomers of AA. A major enrichment in N relative to C occurred during decomposition. Net increases of AS, AA, and bacterial biomarkers in decaying detritus were observed. Three independent approaches indicated that on average 60-75% of the N and 20-40% of the C in highly decomposed detritus were not from the original plant tissues but were mostly from heterotrophic bacteria. During decomposition hydrolyzable AS + AA yields (?54% of total N) were strongly correlated with total N in both types of detritus. The uncharacterized N appeared to have the same origin and dynamics as AA, suggesting the contribution of other bacterial biomolecules not measured here. There was little indication of humification or abiotic processes. Instead, N-immobilization appeared primarily bacterially mediated. Although varying dynamics were observed among individual molecules, bacterial detritus exhibited an average reactivity similar to plant detritus. Only a minor fraction of the bacterial detritus escaped rapid biodegradation and the relationship between bacterial activity and N-immobilization is consistent with an enzymatically mediated preservation mechanism. Bacteria and their remains are ubiquitous in all ecosystems and thus could comprise a major fraction of the preserved and uncharacterized organic matter in the environment. ? 2005 Elsevier Inc. All rights reserved.
Keywords: DECOMPOSITION; DETRITUS; MICROBIAL ACTIVITY; ORGANIC MATTER; AVICENNIA GERMINANS; BACTERIA (MICROORGANISMS); SPARTINA ALTERNIFLORA; TRACHEOPHYTA